Effect of laser on the remnant liver after the first 24 hours following 70% hepatectomy in rats - Barbosa,Ailton Jose (2011)
PURPOSE: To evaluate the mitochondrial function of the remnant liver (RL) in the early phase of liver regeneration in rats after 70% partial hepatectomy (PH). METHODS: Sixty male Wistar rats (200-250g) submitted to 70% PH were divided into five groups according to the time of euthanasia and application or not of laser light: C = Control, time zero; 2 minutes, 4, 6 and 24 hours after PH. The dose of laser radiation was 22.5 J/cm², wavelength of 660 nm (visible/red), in the remnant liver. We studied the respiration activated by ADP (state 3), basal mitochondrial respiration (state 4), respiratory control ratio (RCR) and mitochondrial membrane potential (MMP). RESULTS: The mitochondrial function of RL changed at 4 and 6 hours after PH, with a significant increase in state 3 and a concomitant increase in state 4 and with maintenance of RCR. MMP differed significantly between the groups biostimulated with laser radiation and the control group 4 hours after HP, with a substantial reduction in the non-laser groups. CONCLUSION: The laser light at the dose used in this study did not induce additional damage to the RL and seems to have delayed the hepatocellular metabolic overload of the remnant liver.